Some aspects of the electrochemical formation of carbon micro-tubes from molten chlorides - Yaghmaee M.S.; Demeter Z.S.; Sytchev J.; Lakatos J.; Kaptay G. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Carbon nano/micro-tubes have been successfully synthesized by an electrochemical way from the NaCl-KCl-5% MgCl2 molten salt on the surface of a graphite cathode. The length of the tubes is above 100 µm, while their diameter ranges from hundreds of nanometers to 1-2 µm. A new cleaning procedure of the carbon tubes from the remaining salt has been developed with acetone found to be the best cleaning agent. It has been shown that in addition to carbon micro-tubes, some tube-like or rod-like structures can be formed, which do not actually consist of carbon but of the remained salt.